Leadership Style, Commitment, and Work Motivation on Job Satisfaction and Teacher Performance at the Vocational School of Multi Mekanik Masmur Pekanbaru - Devi Gusriani; Dadi Komardi; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study was to examine the effect of leadership style, commitment, and motivation on job satisfaction and teacher performance at SMK Multi Mekanik Masmur Pekanbaru. Respondents in this study used a sample of 81 people, with a purposive sampling technique as exogenous variables are leadership style, commitment, and motivation. While the endogenous variables are job satisfaction and teacher performance. The data analysis technique used descriptive analysis and hypothesis analysis with structural equation modeling (SEM) and PLS. The results obtained indicate that there is an insignificant effect of leadership style on job satisfaction, commitment has no significant effect on job satisfaction, and motivation has no significant effect on job satisfaction. Furthermore, leadership style has a significant effect on teacher performance, commitment has no significant effect on teacher performance, motivation has no significant effect on teacher performance and job satisfaction has no significant effect on teacher performance.